Investigate Air Well Turbines Performance for Power Generation by Tidal Waves in River - Sharif, Elaff F.; Mahmoud, Mahmoud Sh.; AL-Maskari, Abdullah A. K (Al-Nahrain Journal for Engineering Sciences, 2023)
The phenomenon of climate change resulting from the increase of global warming has become one of the main problems facing the world. Where researchers and specialists have worked for many years to find a solution that reduces this phenomenon and limits its risks. It is likely that clean energy is an alternative to fossil fuel sources, which are the main source of global warming. One of the clean energy sources is ocean wave energy, which is a huge and untapped energy source, despite the possibility of extracting large energy from waves. This paper focuses on the study of deep-sea turbines and their results. A study was conducted on the capture chamber. Where this paper presents an experimental model of a water tank with certain dimensions in the university laboratories to describe the dynamic behavior of the capture chamber. The Froude number scale was used to model the dimensions and depth of the water as well as the wave properties. Through experimental work and its results show, and it was found that the power generated by the motion of the wave strength is related to the height and frequency of the wave.